Evaluating the incidence, risk factors and glycaemic control of new-onset diabetes mellitus in kidney transplant recipients: a single centre study - Siok Wah Lai, Chee Ping Chong, Noorizan Abdul Aziz (Journal of Applied Pharmaceutical Science, 2013)
This study aimed to evaluate the incidence and risk factors for development of post-kidney transplant diabetes mellitus (PTDM) and its glycaemic control in a single centre. Adult kidney transplant recipients (n = 164) under follow-up at Penang Hospital, Malaysia since transplantation (mean follow-up time: 11.04±6.26 years) were retrospectively reviewed. Data were retrieved from year 1984 to 2010. PTDM was defined according to the American Diabetes Association Guideline. Clinical covariates of PTDM were determined by using binary logistic regression analysis. Thirty six patients (22.0%) developed PTDM with a cumulative incidence of 5.5%, 6.7%, 12.2% and 17.7% respectively at 1, 3, 5 and 10 years post-transplantation. Multivariate analysis showed that the number of concurrent diseases in the patients (OR = 2.26, p = 0.007) and fasting blood sugar (FBS) level at 6 months post-transplant (OR = 4.10, p = 0.001) were independent predictors of PTDM. The mean FBS level at the time of diagnosis for PTDM was 11.21±5.57 mmol/L. Treatments with anti-diabetic drug(s) were given and the FBS levels were under controlled (mean value of 6.50±1.14 mmol/L) at six months after the PTDM diagnosis. Close monitoring of blood sugar level particularly early after kidney transplantation is necessary for the detection of PTDM.
Keywords: Post-kidney transplantation, diabetes mellitus, risk